2022
DOI: 10.3390/molecules27207026
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Essential Oil-Based Anticholinesterase Insecticides against Anopheles Vectors: A Review

Abstract: The insect nervous system is critical for its functional integrity. The cholinergic system, of which acetylcholinesterase (AChE) is a key enzyme, is essential to the Anopheles (consisting of major malaria vector species) nervous system. Furthermore, the nervous system is also the primary target site for insecticides used in malaria vector control programs. Insecticides, incorporated in insecticide-treated nets and used for indoor residual spraying, are a core intervention employed in malaria vector control. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 187 publications
0
6
0
Order By: Relevance
“…Diferent phytochemicals are known to cause neurotoxicity or direct contact toxicity to the midgut epithelium of mosquito larvae [34]. In the present study, the identifed essential oil constituents such as caryophyllene oxide, α-pinene, and linalool are known to have antiacetylcholinesterase activity [5], whereas α-terpineol was reported to have an infuence on the production of cyclic adenosine monophosphate (cAMP) and calcium at the cellular level and these efects consequentially lead to larval death [35].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Diferent phytochemicals are known to cause neurotoxicity or direct contact toxicity to the midgut epithelium of mosquito larvae [34]. In the present study, the identifed essential oil constituents such as caryophyllene oxide, α-pinene, and linalool are known to have antiacetylcholinesterase activity [5], whereas α-terpineol was reported to have an infuence on the production of cyclic adenosine monophosphate (cAMP) and calcium at the cellular level and these efects consequentially lead to larval death [35].…”
Section: Resultsmentioning
confidence: 72%
“…In this regard, community-based long-lasting insecticidal nets (LLINs) and larval source management (LSM) have been the mainstay in vector control eforts [4]. However, these synthetic insecticidebased methods are threatened because of widespread resistance to all currently used insecticides by mosquitoes, and their negative efect on the nontarget organisms and the ecosystem [5]. Tese problems may lead to renewed malaria outbreaks and deaths from insecticidal poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Being a mixture of components, essential oils are complex and may have multiple larvicidal mechanisms acting in combination that have not been elucidated [ 19 ]. Some studies have demonstrated that essential oils inhibit acetylcholinesterase, causing neurotoxicity and leading to larval mortality [ 20 ]. In the present study, we measured the acetylcholinesterase activity of larvae after treatment with LC50 of perilla essential oil and 2-hexanoylfuran but found no change ( Figure S2 in Supplementary Materials ).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying insecticide activity in natural products has been a strong focus of recent research, including characterization of components in essential oils, seaweed, botanicals, and medicinal plants [ 57 , 58 , 59 , 60 , 61 ]. Studies have also shown efficacy targeting specific tissues and metabolic pathways, with a focus on new mechanisms of action and avoiding off-target effects.…”
Section: Introductionmentioning
confidence: 99%